1996
DOI: 10.1007/s003359900048
|View full text |Cite
|
Sign up to set email alerts
|

A locus on the X Chromosome is linked to body length in mice

Abstract: Linkage between body length (anus to nose (AN) length) and three markers on the mouse X Chromosome was found in an interspecific backcross ((C57BL/6J x Mus spretus) F 1x C57BL/6J), designated BSB. A cross of 409 mice were scored for 148 genetic markers distributed on all chromosomes except the Y Chromosome. Statistical analysis revealed highly significant linkage (LOD score 5.5) between body length and a locus in the middle portion of the X Chromosome, the nearest markers being the microsatellite marker DXMit7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…This is one of the reasons that we have included all these loci into the analysis of interaction between pairs of markers linked with the analyzed traits. Additional support for the existence of QTLs on growth and obesity detected in this linkage analysis is provided by results from other QTL mapping studies for several different loci (West et al 1994;Warden et al 1995;Cheverud et al 1996;Keightley et al 1996;Lembertas et al 1996Lembertas et al , 1997Phillips 1996, 1997;Rance et al 1997;Kirkpatrick et al 1998;Mehrabian et al 1998;Moody et al 1999;Morris et al 1999;Horvat et al 2000).…”
Section: Discussionmentioning
confidence: 85%
“…This is one of the reasons that we have included all these loci into the analysis of interaction between pairs of markers linked with the analyzed traits. Additional support for the existence of QTLs on growth and obesity detected in this linkage analysis is provided by results from other QTL mapping studies for several different loci (West et al 1994;Warden et al 1995;Cheverud et al 1996;Keightley et al 1996;Lembertas et al 1996Lembertas et al , 1997Phillips 1996, 1997;Rance et al 1997;Kirkpatrick et al 1998;Mehrabian et al 1998;Moody et al 1999;Morris et al 1999;Horvat et al 2000).…”
Section: Discussionmentioning
confidence: 85%
“…The region at Chr X is especially interesting since previous investigators have shown that this region contains many QTLs that are related to the regulation of the size of the entire body 24,25 or the weight of individual organs including liver, heart, and kidney, especially in mice at young age. 26,27 The possible role of the X chromosome in regulation of thymus size is also implicated by previous results by Jones et al 16 who reported a larger thymus in female, but not male, B6 mice compared to D2 mice.…”
Section: Discussionmentioning
confidence: 99%
“…Warden et al [123] reported a QTL for adult body weight on chromosome 7 in a Spretus × C57 backcross (designated BSB) of 412 mice. Using 252 mice from the same cross, Lembertas et al [77] identified a QTL for body length on chromosome X that had no significant effect on body composition. This QTL probably maps to a similar location to the QTL found by Rance et al [103].…”
Section: Experimental Qtl Studies In Micementioning
confidence: 99%